Anxiety Disorders and Prediction of Their Development in Patients with Hypothyroidism and Autoimmune Thyroiditis - Kamyshna, Iryna; Pavlovych, Larysa; Pankiv, Volodymyr; Pankiv, Ivan; Kamyshnyi, Aleksandr (Open Access Macedonian Journal of Medical Sciences, 2022)
Objective: Since the association between thyroid dysfunction and neuropsychiatric disorders has been known for many years, it is important to analyze the associations of the BDNF gene polymorphism (rs6265), the VDR gene polymorphism (rs2228570), and the NMDA gene polymorphism (rs4880213) with the anxiety in patients with autoimmune thyroiditis and hypothyroidism in the Western Ukrainian population and predict the development of anxiety disorders in these patients. Methods: The study involved a total of 153 patients with various forms of thyroid pathology. BDNF levels in the sera of the patients and healthy individuals were quantified using an enzyme-linked immunosorbent assay with a highly sensitive Human BDNF ELISA Kit (Elabscience®, United States, Catalog No: E-EL-H0010) on E.I.A. Reader Sirio S (Seac, Italy). Genotyping of the VDR (rs2228570), BDNF (rs6265), and NMDA (rs4880213) gene polymorphism using TaqMan probes and TaqMan Genotyping Master Mix (4371355) on CFX96™Real-Time PCR Detection System (Bio-Rad Laboratories, Inc., USA). Polymerase chain reaction (PCR) for TaqMan genotyping was carried out according to the kit instructions (Applied Biosystems, USA). Results: According to the data obtained when comparing the presence of anxiety on the Hamilton scale on SNP statistically significant differences were revealed depending on BDNF gene polymorphism (rs6265) (p < 0.001). When comparing the presence of anxiety on the Hamilton scale on SNP depending on VDR gene polymorphism (rs2228570), NMDA gene polymorphism (rs4880213) no statistically significant differences were revealed (p = 0.782, p = 0.677 respectively) We identified an inverse strong correlation between the presence of anxiety on Hamilton scale and BDNF, 25-OH Vitamin D levels, and fT4 in the blood (p <0.001) and a direct moderate correlation between the presence of anxiety on Hamilton scale and TSH, GRIN2B, and anti-TPO (p <0.001). Conclusion: Indicators such as BDNF, GRIN2B, fT4, anti-TG, and 25-OH levels of vitamin D are prognostically significant risk criteria for anxiety.